The Effect of Anti-fraud Socialization, Whistleblowing System, and Social Sanction on Assets Misappropriation - Aiman, Rahmat; Roekhudin, Roekhudin; Subekti, Imam (Institut Teknologi dan Bisnis Asia Malang, 2025)
Based on the AFCE report (2022), asset misappropriation is identified as the most prevalent form of fraud across all sectors. However, unlike other types of fraud, research addressing methods to mitigate asset misappropriation remains limited. This study aims to conduct empirical testing regarding the influence of anti-fraud socialization, whistleblowing systems, and social sanctions on asset misappropriation. This study uses a quantitative approach by utilizing primary data collected through questionnaires. The sample size in this research consists of 158 respondents who are employees of Regional Government Agencies of South Sulawesi. Hypothesis testing was conducted using the Smart-PLS application, employing bootstrapping techniques to estimate the path coefficients of each variable. The result showed that (1) anti-fraud socialization has a negative effect on asset misappropriation; (2) whistleblowing systems do not have a significant impact on asset misappropriation, and (3) social sanctions have a negative effect on asset misappropriation.